Disordered eating in Sami and non-Sami Norwegian populations: the SAMINOR 2 Clinical Survey - Kvaløy, Kirsti; Melhus, Marita; Silviken, Anne; Brustad, Magritt; Sørlie, Tore; Broderstad, Ann Ragnhild (Public Health Nutrition, 2017)
Source at https://doi.org/10.1017/S1368980017003597 . Objective : The present study aimed to investigate disordered eating (DE) among Sami compared with non-Sami residing in northern Norway. Design : In a cross-sectional design, stratified by sex and ethnicity, associations were tested between DE (Eating Disturbance Scale; EDS-5) and age, education level, BMI category, anxiety and depression, physical activity and consumption of snacks. Setting : The SAMINOR 2 Clinical Survey (2012–2014) based on the population of ten municipalities in northern Norway. Subjects : Adults aged 40–69 years; 1811 Sami (844 male, 967 female) compared with 2578 non-Sami (1180 male, 1398 female) individuals. Results : No overall significant ethnic difference in DE was identified, although comfort eating was reported more often by Sami individuals (P=0·01). Regardless of ethnicity and sex, symptoms of anxiety and depression were associated with DE (P<0·001). Furthermore, DE was more common at lower age and higher BMI values. Education levels were protectively associated with DE among Sami men (P=0·01). DE was associated (OR, 95% CI) with low physical activity in men in general and in non-Sami women (Sami men: 2·4, 1·4, 4·0; non-Sami men: 2·2, 1·4, 3·6; non-Sami women: 1·8, 1·2, 2·9) and so was the consumption of snacks (Sami men: 2·6, 1·3, 5·0; non-Sami men: 1·9, 1·1, 3·1; non-Sami women: 2·1, 1·3, 3·4). Conclusions : There were no significant differences regarding overall DE comparing Sami with non-Sami, although Sami more often reported comfort eating. There were significant sex and ethnic differences related to DE and physical activity, snacking and education level.